Implikasi Kebersihan terhadap Motivasi Belajar Siswa di SDN 2 Loktabat Utara - Nadya Astuti (Departement of Mathematics Education, 2023)
The environment is a place or room that can influence the student learning process. Without a clean environment, student learning motivation is also less than optimal. This study aims to determine the implications of school cleanliness on students' learning motivation at SDN 2 Loktabat Utara. This research method is qualitative research with data collection techniques using observation, interviews and documentation. teachers who might be able to become material to support research and some students at SDN 2 Loktabat Utara. The results of this study indicate that with a clean school environment, that children's learning motivation can develop quickly, that students are more comfortable with school conditions and clean class. It can be said that SDN 2 Loktabat Utara has a clean environment, so it is able to increase student learning motivation, students are more comfortable when the school environment and class are clean, so learning activities in class will be more enthusiastic and maximal.